2022
DOI: 10.3847/1538-4357/ac795b
|View full text |Cite
|
Sign up to set email alerts
|

ALMA Reveals Extended Cool Gas and Hot Ionized Outflows in a Typical Star-forming Galaxy at Z = 7.13

Abstract: We present spatially resolved morphological properties of [C II] 158 μm, [O III] 88 μm, dust, and rest-frame ultraviolet (UV) continuum emission for A1689-zD1, a strongly lensed, sub-L* galaxy at z = 7.13, by utilizing deep Atacama Large Millimeter/submillimeter Array (ALMA) and Hubble Space Telescope (HST) observations. While the [O III] line and UV continuum are compact, the [C II] line is extended up to a radius of r ∼ 12 kpc. Using multi-band rest-frame far-infrared continuum data ranging from 52 to 400 μm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 104 publications
3
18
0
Order By: Relevance
“…The dust temperature drops with increasing radius as seen in the top-left panel. A similar dependence is found in a star-forming galaxy at z = 7.13 (Akins et al 2022). We fit a power law, T dust ∝ r −0.41±0.20 .…”
Section: Dust Diagnosticsupporting
confidence: 79%
“…The dust temperature drops with increasing radius as seen in the top-left panel. A similar dependence is found in a star-forming galaxy at z = 7.13 (Akins et al 2022). We fit a power law, T dust ∝ r −0.41±0.20 .…”
Section: Dust Diagnosticsupporting
confidence: 79%
“…We caution, however, that the spectroscopic blueshift and the ≈2σ spatial offset of [C II] relative to the UV component and [O III] emission (Fujimoto et al 2022b) indicate that the origin of the [C II] emission is not fully co-spatial with the most intense, star-forming region of the galaxy. Such extended, blueshifted [C II] emission has been observed in other high-z galaxies, and may hint at an offsetan abundant gas reservoir, a shock-heated outflowing gas, or minor mergers (e.g., Maiolino et al 2015;Kohandel et al 2019;Arata et al 2020;Akins et al 2022;Katz et al 2022). The latter scenario would typically produce much broader (>1000 km s −1 ) [C II] line profiles (Appleton et al 2013), whereas the observed narrow-line feature is consistent with the low stellar mass of S04590.…”
Section: The Total Dynamical Masssupporting
confidence: 63%
“…We (Smit et al 2018;Fujimoto et al 2019;Matthee et al 2019;Carniani et al 2020;Akins et al 2022;Fudamoto et al 2022), though S04590 presents one of the most notable cases with r e,[CII] ≈ 10 × r e,UV . Assuming the "disk" diameter is D [CII] = 2 × r e,[CII] , we infer D [CII] = 2.2 ± 1.4 kpc.…”
Section: The Total Dynamical Massmentioning
confidence: 99%
“…While [CII] emission in distant galaxies has been observed to be more spatially extended than the [OIII] emission (e.g., Carniani et al 2020;Akins et al 2022; Section 6.1), we note that our results remain unchanged if we re-extract the [CII] fluxes following the procedure adopted for the [OIII] line described in Section 3. This is as expected, given that the fluxes are extracted in an aperture with a radius of ∼ 10 kpc at 𝑧 = 7, which is much larger than the typical [CII] sizes of galaxies of 𝑟 [CII] ∼ 2 kpc (Fujimoto et al 2020;Fudamoto et al 2022b).…”
Section: [Oiii] Emissionmentioning
confidence: 58%